High electronic couplings of single mesitylene molecular junctions - Komoto, Yuki; Fujii, Shintaro; Nishino, Tomoaki; Kiguchi, Manabu (Beilstein Journal of Nanotechnology, 2015)
We report on an experimental analysis of the charge transport properties of single mesitylene (1,3,5-trimethylbenzene) molecular junctions. The electronic conductance and the current–voltage characteristics of mesitylene molecules wired into Au electrodes were measured by a scanning tunnelling microscopy-based break-junction method at room temperature in a liquid environment. We found the molecular junctions exhibited two distinct conductance states with high conductance values of ca. 10−1G0 and of more than 10−3G0 (G0 = 2e2/h) in the electronic conductance measurements. We further performed a statistical analysis of the current–voltage characteristics of the molecular junctions in the two states. Within a single channel resonant tunnelling model, we obtained electronic couplings in the molecular junctions by fitting the current–voltage characteristics to the single channel model. The origin of the high conductance was attributed to experimentally obtained large electronic couplings of the direct π-bonded molecular junctions (ca. 0.15 eV). Based on analysis of the stretch length of the molecular junctions and the large electronic couplings obtained from the I–V analysis, we proposed two structural models, in which (i) mesitylene binds to the Au electrode perpendicular to the charge transport direction and (ii) mesitylene has tilted from the perpendicular orientation.
Keywords: break junction; charge transport; mesitylene; single molecular junction; scanning tunnelling microscopy (STM)